Detection of multiple sclerosis lesions in the cervical cord: which of the MAGNIMS 'mandatory' non-gadolinium enhanced sagittal sequences is optimal at 3T?. Issue 6 (December 2021) - Chang, Chian A; Chong, Abigail L; Chandra, Ronil V; Butler, Ernest; Rajendran, Deepa; Chuah, Kenneth; Stuckey, Stephen
Background and purpose: The magnetic resonance imaging in multiple sclerosis consensus guidelines currently mandate three sagittal non-contrast enhanced sequences of T2-weighted fast spin echo, proton density-weighted fast spin echo and short tau inversion recovery; however, these particular three sequences have not previously been compared at 3T. This study compared T2-weighted fast spin echo, proton density-weighted fast spin echo, short tau inversion recovery as well as the double inversion recovery sequence for the sagittal detection of multiple sclerosis lesions in the cervical spinal cord at 3T. Methods: Nineteen multiple sclerosis patients underwent magnetic resonance imaging with 3T sagittal T2-weighted fast spin echo, proton density-weighted fast spin echo, short tau inversion recovery and double inversion recovery between November 2012 and April 2013. Two neuroradiologists independently reviewed the images, and the number of lesions detected on each sequence was recorded. Lesion conspicuity was quantitatively assessed with the lesion-to-cord-contrast ratio and lesion contrast-to-noise ratio. The Wilcoxon signed rank test was performed for statistical analysis. Results: Proton density-weighted fast spin echo and short tau inversion recovery detected 32% more lesions compared to T2-weighted fast spin echo, and 37% more lesions compared to double inversion recovery. The lesion-to-cord-contrast ratio was highest in short tau inversion recovery, while the lesion contrast-to-noise ratio was highest for proton density-weighted fast spin echo. Conclusions: This study provides the necessary evidentiary support at 3T for the magnetic resonance imaging in multiple sclerosis spinal magnetic resonance imaging protocol consensus guidelines. At 3T sagittal proton density-weighted fast spin echo and short tau inversion recovery sequences allowed improved detection of cervical spinal cord multiple sclerosis lesions, compared to T2-weighted fast spin echo and three-dimensional double inversion recovery magnetic resonance imaging. Utilising T2-weighted fast spin echo alone at 3T is insufficient for lesion detection.